Life insurance demand under health shock risk - Holger Kraft; Lorenz S. Schendel; Mogens Steffensen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
This paper studies the life cycle consumption-investment-insurance problem of a family. The wage earner faces the risk of a health shock that significantly increases his probability of dying. The family can buy term life insurance with realistic features. In particular, the available contracts are long term so that decisions are sticky and can only be revised at significant costs. Furthermore, a revision is only possible as long as the insured person is healthy. A second important and realistic feature of our model is that the labor income of the wage earner is unspanned. We document that the combination of unspanned labor income and the stickiness of insurance decisions reduces the insurance demand significantly. This is because an income shock induces the need to reduce the insurance coverage, since premia become less affordable. Since such a reduction is costly and families anticipate these potential costs, they buy less protection at all ages. In particular, young families stay away from life insurance markets altogether.
urn:nbn:de:hebis:30:3-331503
Keywords: D14; D91; G11; G22; 330; Health shocks; Portfolio choice; Term life insurance; Mortality risk; Labor income risk